2011
DOI: 10.1128/jvi.00542-11
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Accumulation of the Papillomavirus E1 Helicase Blocks S-Phase Progression and Triggers an ATM-Dependent DNA Damage Response

Abstract: Replication of the papillomavirus genome is initiated by the assembly of a complex between the viral E1 and E2 proteins at the origin. The E1 helicase is comprised of a C-terminal ATPase/helicase domain, a central domain that binds to the origin, and an N-terminal regulatory region that contains nuclear import and export signals mediating its nucleocytoplasmic shuttling. We previously reported that nuclear accumulation of E1 has a deleterious effect on cellular proliferation which can be prevented by its nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
161
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(173 citation statements)
references
References 89 publications
12
161
0
Order By: Relevance
“…In this way, ssDNA may be generated, stimulating activation of the ATR/ Chk1 pathway. Interestingly, transfected papillomavirus E1 alone or with E2 is sufficient for activation of both ATR and ATM (32,34). In light of the present results, it is conceivable that aphidicolin uncouples pol␣ and E1, resulting in a stalled, unstable replication fork.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…In this way, ssDNA may be generated, stimulating activation of the ATR/ Chk1 pathway. Interestingly, transfected papillomavirus E1 alone or with E2 is sufficient for activation of both ATR and ATM (32,34). In light of the present results, it is conceivable that aphidicolin uncouples pol␣ and E1, resulting in a stalled, unstable replication fork.…”
Section: Discussionmentioning
confidence: 79%
“…Acting downstream of ATM and ATR are the Chk2 and Chk1 kinases, respectively, which phosphorylate a host of substrates to coordinate the DDR (30). Elements of both the ATM and ATR pathways are activated in HPV-positive cells, and a role for ATM activation has been implicated in productive HPV DNA replication (31)(32)(33)(34).…”
mentioning
confidence: 99%
“…In the maintenance phase, minimal expression of viral proteins in host cells with low copy numbers of viral genomes would allow HPV to evade cellular immune surveillance. Moreover, as recent studies indicate, a high level of E1 expression in basal-layer cells could activate an ATM-dependent damage response and cause growth suppression (10,32).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, an HPV variant promoting an increase in viral replication could have a diminished transforming potential. Furthermore, Fradet-Turcotte et al (2011) demonstrated that the nuclear export of E1 is required for the maintenance of the viral genome in undifferentiated keratinocytes but not for its amplification in differentiated cells, suggesting that the increased levels of E1 in the nucleus could create a favourable environment for viral DNA amplification by blocking cells in the S-phase. This blockage would induce DNA damage response by ATM-dependent pathway, promoting DNA repair or leading to apoptosis.…”
Section: (B)mentioning
confidence: 99%